2022
DOI: 10.3390/polym14214659
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Fiber-Reinforced Polymer Composites by Fused Deposition Modelling (FDM): Fiber Length and Fiber Implementation Techniques

Abstract: Fused Deposition Modelling (FDM) is an actively growing additive manufacturing (AM) technology due to its ability to produce complex shapes in a short time. AM, also known as 3-dimensional printing (3DP), creates the desired shape by adding material, preferably by layering contoured layers on top of each other. The need for low cost, design flexibility and automated manufacturing processes in industry has triggered the development of FDM. However, the mechanical properties of FDM printed parts are still weaker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 156 publications
0
16
0
Order By: Relevance
“…FDM as shown in Fig. 1 has become increasingly popular in industrial applications such as biomedical, mechanical, and electrical manufacturing in recent years [16,[20][21][22].…”
Section: Fibresmentioning
confidence: 99%
See 1 more Smart Citation
“…FDM as shown in Fig. 1 has become increasingly popular in industrial applications such as biomedical, mechanical, and electrical manufacturing in recent years [16,[20][21][22].…”
Section: Fibresmentioning
confidence: 99%
“…From the tensile and flexural strength results, it can be concluded that a smaller fibre size is better than a larger fibre size. A smaller size has a higher surface area to increase the bonding between the two phases and can distribute well without agglomeration thus increasing the inner strength of the composites [22]. The trend of strength that gradually decreases as the size of the fibre is increasing might be due to voids or impurities of the fibre itself.…”
Section: Mechanical Testingmentioning
confidence: 99%
“…Manufacturers prefer these techniques according to the dimensions of the applications to be made. Fused Deposition Modeling (FDM) [ 23 , 24 ], SLA [ 25 , 26 ], Polyjet [ 27 ], Selective Laser Sintering (SLS) [ 28 ], Inkjet Printing [ 29 ], Digital Light Processing (DLP) [ 30 ], and Two-Photon Polymerization (TPP) [ 31 , 32 ] are the most widely used 3D printing techniques today. In particular, TPP, SLA, and DLP techniques were found to be superior to other methods in the fabrication of micro and nano systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, most 3D printed polymer products are still used as conceptual prototypes rather than functional components because unreinforced polymer products built by FDM lack strength and functionality (Chacón et al , 2019). To improve the mechanical performance of 3D printed parts, fibres have been added to polymers (Ismail et al , 2022). The development of short fibre-reinforced polymer composites made by additive manufacturing has been on-going for about a decade (Goh et al , 2019; Zindani and Kumar, 2019).…”
Section: Introductionmentioning
confidence: 99%